Os efeitos do acordo de associação transpacífico (TTP) e do acordo de parceria transatlântico de comércio e investimento (TTIP) sobre o mercado internacional de fertilizantes - Bosio, Eric Losala (2018)
The present study aims to evaluate the possible impacts of eliminating tariff barriers on the fertilizer market. To evaluate the effects of free trade is used a spatial model formulated as Mixed Complementary Problem (MCP). To achieve the proposed objective, five scenarios are simulated: the first considers the elimination of tariff barriers in a multilateral arrangement; the second simulates the expansion of the Transatlantic Trade and Investment Partnership Agreement (TTIP), including Brazil in the agreement; the third simulates the inclusion of Brazil in the Trans-Pacific Association Agreement (TTP); the fourth simulates the formation of a bilateral agreement that eliminates trade barriers between Brazil and Russia; and the fifth simulates an agreement between Brazil and the region of Africa. The biggest gains are in the scenario where the elimination of all tariff barriers in a multilateral trade agreement is considered, which means that for the fertilizer market the elimination of tariff barriers in a multilateral trading arrangement is the best option for production for all producers than regional arrangements.